2016
DOI: 10.1016/j.jtcme.2014.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Assessed Chronic Illness Care (PACIC) scenario in an Indian homeopathic hospital

Abstract: Homeopathy research has focused on chronic conditions; however, the extent to which current homeopathic care is compliant with the Chronic Care Model (CCM) has been sparsely shown. As the Bengali Patient-Assessed Chronic Illness Care (PACIC)-20 was not available, the English questionnaire was translated and evaluated in a government homeopathic hospital in West Bengal, India. The translation was done in six steps, and approved by an expert committee. Face validity was tested by 15 people for comprehension. Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It is contrary to the original validation study scores that were positively associated with gender and the number of chronic diseases [ 23 ]. Findings of the study in India showed that PACIC 20 was slightly correlated with age, gender and chronic diseases [ 30 ]. A Swiss study showed the significant correlation between the French version of the PACIC and age [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is contrary to the original validation study scores that were positively associated with gender and the number of chronic diseases [ 23 ]. Findings of the study in India showed that PACIC 20 was slightly correlated with age, gender and chronic diseases [ 30 ]. A Swiss study showed the significant correlation between the French version of the PACIC and age [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its test–retest reliability (0.58), internal consistency (0.93) and convergent validity (0.42–0.60) have been demonstrated in varied chronic condition patient populations including hypertension, depression, diabetes, asthma, and chronic pain 49,50,52. Only one study reported a responsiveness of 1.11 (standardized response mean) 53. The PACIC is scored by averaging scores across all 20 items 52.…”
Section: Methodsmentioning
confidence: 99%
“…In order to maintain the functionality of the elderly, it is essential to optimize the management of chronic conditions. This requires multidimensional strategies anchored in the concept of health conditions and with theoretical references related to patient-centered care 4 - 5 , which is not always observed. Studies have shown a persistent care practice aimed at treating the conditions and events resulting from the exacerbation of chronic conditions, in a fragmented, episodic and reactive manner 6 .…”
Section: Introductionmentioning
confidence: 99%